2021
DOI: 10.3389/fmed.2021.645543
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pathology Patterns in Persons Who Died From COVID-19 in Italy: A National Study Based on Death Certificates

Abstract: Background: In Italy, during the first epidemic wave of 2020, the peak of coronavirus disease 2019 (COVID-19) mortality was reached at the end of March. Afterward, a progressive reduction was observed until much lower figures were reached during the summer, resulting from the contained circulation of SARS-CoV-2. This study aimed to determine if and how the pathological patterns of the individuals deceased from COVID-19 changed during the phases of epidemic waves in terms of: (i) main cause of death, (ii) comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…Italy was one of the countries more severely hit by the first COVID-19 pandemic wave in early 2020. So far, in Italy, mortality studies have focused on comorbidities reported in small groups of death certificates of patients with COVID-19 [ 12 , 13 ] or on broad categories of CoDs in small geographical areas [ 14 , 15 ]. The availability of data from the national CoD register represents a unique opportunity for a full analysis of the impact of the pandemic on the most common CoDs.…”
Section: Introductionmentioning
confidence: 99%
“…Italy was one of the countries more severely hit by the first COVID-19 pandemic wave in early 2020. So far, in Italy, mortality studies have focused on comorbidities reported in small groups of death certificates of patients with COVID-19 [ 12 , 13 ] or on broad categories of CoDs in small geographical areas [ 14 , 15 ]. The availability of data from the national CoD register represents a unique opportunity for a full analysis of the impact of the pandemic on the most common CoDs.…”
Section: Introductionmentioning
confidence: 99%
“…114 While we identified only one COVIDrelated article (due to the timing of our database search), multiple-cause methods have since been applied to ascertain associations between contributing conditions and complications, assess changes in the pathological patterns, and identify noteworthy sociodemographic variation in COVID-related deaths, [115][116][117][118] leading in some circumstances to improved survival. 119 Importantly, the recent emergence of COVID-19 as a leading underlying cause 120 may substantially alter proportional mortality from other underlying causes. As such future analyses of multiple causes will be necessary for monitoring trends in COVID-related mortality as well as the impact of COVID-19 on other causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…110 While we identified only one COVID-related article (due to the timing of our database search), MC methods were since applied to ascertain associations between contributing conditions and complications, assess changes in the pathological patterns, and identify significant sociodemographic variation in COVID-related deaths, [111][112][113][114] leading in some circumstances to improved survival. 115 Importantly, the recent emergence of COVID-19 as a leading UC 116 may significantly alter proportional mortality from other UCs. As such future analyses of multiple causes will be necessary for monitoring trends in COVID-related mortality as well as the impact of COVID-19 on other causes of death.…”
Section: Discussionmentioning
confidence: 99%